Preserved fuel mix in spite of increased metabolic rate and lactate steady state at higher cycling cadence - Beneke, R.; Leithäuser, R. M.; Peters, K.; Beier, T.; Caputo, F. (International Journal of Sports Physiology and Performance, 2025)
Purpose: To assess the effects of cycling cadence, exercise intensity, and preload on blood lactate concentration (BLC), carbohydrate oxidation (CHO), and gross efficiency (GE) during 60-minute cycling sessions.